ROLE OF HIF-1 SIGNALING PATHWAY IN CELLULAR ADAPTATION TO HYPOXIA - Kamil Borysewicz,; Illia Koval,; Wiktor Kubik,; Bartłomiej Czarnecki,; Jan Nowak,; Barbara Kujawa,; Bartosz Zwoliński,; Kacper Sukiennicki,; Wirginia Bertman,; Natalia Kołdej,; Zuzanna Kępczyńska,; Katarzyna Szewczyk,; et al. (International Journal of Innovative Technologies in Social Science, 2025)
Hypoxia accompanying chronic inflammatory diseases leads to dysregulation of cells’ homeostasis, causes energy deficits and intensifies inflammatory processes. Hypoxia-inducible factors (HIFs) are the central regulators of the response to hypoxia, enabling metabolic and functional adaptation of immune cells by altering gene expression. HIF-1α and HIF-2α modulate the lifespan, differentiation, priming and activation of neutrophils, macrophages, lymphocytes, and dendritic cells- playing a key role in influencing the balance between proinflammatory and reparative responses. Interactions between HIF and NF-κB pathways regulate hypoxic and inflammatory signaling, and as a result determine course, severity and treatment efficacy of many chronic diseases. Those two pathways are capable of influencing each other in a manner of negative feedback-loop. Understanding the mechanisms of this regulation opens up new therapeutic perspectives in the treatment of pulmonary diseases associated with hypoxia and inflammation, and a hypothetical possibility to  slow down the ratio at which chronic inflammatory response contributes to deterioration of patients’ quality of life.